Experimental and FEM Research on Airport Cement Concrete Direct-Thickening Double-Deck Pavement Slabs under Aircraft Single-Wheel Dynamic Loads - Qingkun Yu; Liangcai Cai; Jianwu Wang (Advances in Materials Science and Engineering)
The wide-use airport cement concrete direct-thickening double-deck pavement slabs (ACCDDPS) were selected as the research object to study their mechanical properties. The airport runway simulation test station (ARSTS) was used to conduct indoor tests to demonstrate the distribution of tension stress at the bottom of slabs and slabs deflection. Furthermore, ANSYS software was applied to establish finite element model (FEM) of ACCDDPS and analyze the mechanical laws under different loads. The indoor tests results are in good agreement with the ANSYS simulation results, and some consistent conclusions can be obtained that the maximum tension stress increases with wheel load, and the slab middle of the longitudinal edge is a critical position. In addition, we studied the influence of covered layer thickness, elastic modulus, and slab size on pavement slab mechanical properties by ANSYS, and we concluded that although the structural parameters are different, the critical position of ACCDDPS is still in the middle of the longitudinal edge. However, for the covered layer and the original surface layer, the law that the tension stress values vary with the structural parameters is different, but the maximum deflection value is about 0.1.